Varietal Improvement of Normal Season Irrigated Rice for Eastern Terai Region of Nepal - Prasai, Hari Kumar; Bhattarai, Rudra; Shrestha, Jiban (International Journal of Applied Sciences and Biotechnology, 2017)
Correction: On 4th June 2021 the name of the third author was changed from 'Jivan' to 'Jiban'. The coordinated and regional varietal trial of normal season irrigated rice was carried out at Regional Agricultural Research Station (RARS), Tarahara, Nepal in 2014 & 2015. Out of the tested genotypes, NR 2157-166-1-3-5-1, Cieharang and NR 2157-166-2-1-1-1 identified as promising with potential grain yield of 4313, 4290 and 4239 kg/ha respectively in over year analysis (2014-15) under coordinated varietal trial (CVT). These genotypes recorded 25 to 27 percent higher grain yield than national rice productivity and 4 to 6 percent more than check variety, Sabitri. The differences in grain yield among the tested genotypes and between the years were found significant, but interaction of genotypes to year was found non-significant. Similarly, KARAJAT-3 recorded the highest grain yield (4897 kg/ha) followed by NR 1190-24-4-2-2-2-3-2 (4861 kg/ha) in over year analysis (2014-15) of regional varietal trial (RVT), similarly, identified as promising genotypes. These promising genotypes recorded 43 and 8 percent higher grain yield than national rice yield and to the check variety, Sabitri, respectively in over year analysis. The differences in grain yield among genotypes and year were found significant whereas it was non-significant for interaction of genotypes and to the tested years. Int J Appl Sci Biotechnol, Vol 4(4): 489-497